World politics trend and transformation - Blanton, Shannon Lindsey; Blanton, Shannon Lindsey (Cengage Learning, 2021)
World politics: trend and transformation, 17th Edition, helps you understand what is happening on the international political stage -- and why. Thought-provoking discussions encourage you to critically assess the problems, payoffs, pitfalls and paradoxes of people's choices about the global future and the likely long-term impact of those choices. Coverage includes recent challenges to global peace and prosperity; changes in the political landscape sparked by Brexit, the rise of China and enduring rivalries; terrorism and advances in military capabilities; human rights and inequality; threats to global health and the environment; and more. The Carnegie Council for Ethics in International Affairs provides further insight into emerging issues. Also available: MindTap Political Science digital learning solution.